2020
DOI: 10.20527/flux.v17i1.6394
|View full text |Cite
|
Sign up to set email alerts
|

Potensi Limbah Arang Kayu Alaban (Vitex pubescens Bahl), Abu Dasar dan Abu Terbang Batubara Sebagai Bahan Briket

Abstract: Characterization of wood waste from halaban wood, bottom ash, and coal fly ash has been done includes tests of water content, ash content, calorific value, and composition as well as morphology. One of the factors that influences the characteristics is the powder size. Therefore, this research uses 250 mesh sieve (smaller powder size) to make briquettes. From the test results, the average moisture content was 4.22% for halaban wood charcoal, 1.64% for bottom ash and 0.91% for fly ash. Average ash content of 41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…This study is a continuation of previous research based on the briquette quality standard used, namely SNI 01-6235-2000, about the Quality of Wood Briquettes [14]. From previous studies, the results of the characteristics of coal bottom ash (water content, ash content, calorific value) and the elemental composition and morphology were obtained [8].…”
Section: Methodsmentioning
confidence: 84%
See 2 more Smart Citations
“…This study is a continuation of previous research based on the briquette quality standard used, namely SNI 01-6235-2000, about the Quality of Wood Briquettes [14]. From previous studies, the results of the characteristics of coal bottom ash (water content, ash content, calorific value) and the elemental composition and morphology were obtained [8].…”
Section: Methodsmentioning
confidence: 84%
“…Other research found that the water content, ash content and calorific value of Halaban wood charcoal waste were 4.22%, 41.93%, and 6833.1 cal/gr, respectively. While for coal bottom ash were 1.64%, 82.03% and 389.5 cal/gr [8].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…This shows that the biobriquettes of banana stems and corncobs in this composition have better combustion quality than the biobriquettes of fish bones and bagasse. [19] reported in their study that the lower the levels of SO2, NOx, and CO emitted from the combustion of bio-briquettes, the better the quality of the briquettes.…”
Section: Analysis Of Bio-briquette Combustion Emissionsmentioning
confidence: 99%
“…Fly ash can be used as a mixed material in the manufacture of lightweight concrete bricks. These bricks have good strength, high thermal insulation, and contribute to energy savings (Haryanti, 2017). Fly ash can be used as a material to form a strong and stable landfill foundation (Aditya, 2019).…”
Section: Application Of Fly Ash Waste Utilization In Cement Industrymentioning
confidence: 99%